(untitled) (Revista de Ciências Agroveterinárias, 2020)
This work aimed to evaluate the physical and mechanical properties based panels made of barley industrial waste and particles Pinus spp. The company Bonet Woods and Papers Ltda. in the municipality of Santa Cecilia - Santa Catarina, provided the particles Pinus spp. The barley residue was provided by AMBEV in Lages, SC. For the production of panels used were five treatments, being composed of different barley residue content and particle Pinus spp.: 100:0 (T1), 75:25 (T2), 50:50 (T3), 25:75 (T4) and 0:100 (T5), to the residue and timber respectively. Three panels were produced per treatment, totaling 15 panels. The nominal density of 650 Kg.m-3, 12% of urea formaldehyde resin, 1% paraffin, eight minutes press cycle were used in the production of panels, with a temperature of 160 °C and a maximum pressure of 40 Kgf.cm-2. For the physical properties, moisture content, density, compression ratio, thickness swelling and water absorption (2h and 24h) were determined. The mechanical properties determined were static bending, internal connection, top and surface screw pulling. With the results found it can be concluded that increasing the percentage of barley residue decreases the resistance of the panels to the physical and mechanical properties.